Persuasi Dakwah Youtube Pada Mahasiswa Islam di Kota Surabaya Selama Pandemi - Nanik Mujiati; Muhammad Munir; Ivan Sunata (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2021)
Youtube can make it easy for the public to enjoy and learn the content. The main target students in the use of youtube are good school materials, physical materials that they don't know about in their everyday lives. The aim of this research is how effective the short video in the story of every person who uses as a reminder because the truth of every Muslim is a reminder to other Muslims. With this research it will be useful for the Da’i in a time of much material and more effective long-term education. This type of research is qualitative that uses phenomenological studies in students, data analysis in this study is data reduction and data synthesization. While the group was observing and interviewing. The result of this research is to reveal about Dakwah Media, Youtube Dakwah Media, Youtube Video Adaptation Dakwah on Khalayak, Social Media and Student Self-Concept and the Dakwah symphony through this youtube can also be enjoyed anywhere and whenever. The subject or the indictment also contains the subject that Surabaya students need. As for this youtube persuasion, it's only about invitations or good advice for Surabaya students. The video's neither long nor boring. Surabaya students can also take wisdom or indictment as indictees say.